Internship Regulations in Vocational Secondary Schools during the Covid-19 Pandemic - Andri Setiyawan (VANOS Journal of Mechanical Engineering Education, 2021)
The Covid-19 pandemic has had an impact on the implementation of vocational secondary schools (VSS) internships. The enactment of the area causes internship activities not to run optimally. Vocational secondary schools 1 Mojokerjo provides direction to students in the performance of internship activities. The method used in this research is descriptive exploratory. The result of this study is the regulation of the implementation of internships during the Enforcement of Restrictions on Community Activities (ERCA) period in the East Java region under the Directives of the East Java Provincial Education Office. They rescheduled internship activities that match the student's domicile or location. Students are not allowed to do an internship at the company. Schools encourage students to maintain health protocols and monitor student conditions boldly.